Mapping of failures after radiochemotherapy in patients with non-metastatic esophageal cancer: A posteriori analysis of the dose distribution in the sites of loco-regional relapse. Issue 2 (August 2015) - Bednarek, Coraline; Crehange, Gilles; Quivrin, Magali; Cueff, Adèle; Vulquin, Noémie; Chevalier, Cédric; Cerda, Thomas; Petegnief, Yolande; Mazoyer, Frédéric; Maingon, Philippe; Bosset, Jean François; Servagi Vernat, Stéphanie
Abstract: Background and purpose: We aimed to evaluate the patterns of loco-regional failure (LRF) after exclusive chemoradiotherapy (eCRT) for esophageal cancer with respect to planned dose and/or the incidental (unplanned) dose outside target volumes. Materials and methods: Co-image registration of CT or 18 F-FDG PET-CT at the time of failure (tf) and at the time of CRT (t0) was performed in 34 patients with LRF. Dosimetric parameters with regard to local failure (LF), nodal failure (NF) and involved nodal stations (NS) were derived. Results: Twenty-two patients (64.7%) had LF, the majority of which (95.5%) were located at the epicenter of the GTV of the primary tumor. The mean doses recalculated to the NS at tf were more likely to be lower than the planned dose delivered to the PTV at t0: D mean = 33.9 ± 20.8 Gy vs 52.2 ± 8.5 Gy ( p = 0.0009), D 95% = 27.5 ± 21 Gy vs 46.1 ± 4.8 Gy ( p = 0.004). Among the 12 patients with NF outside the elective nodal irradiation (ENI) volume, D mean of NS outside the ENI was significantly lower (19.4 ± 21.4 Gy) than the D mean of NS with failure within the ENI (45.1 ± 6.1 Gy, p = 0.01). Conclusion: Loco-regional failure after exclusive chemoradiotherapy for esophageal cancer may be due to an inadequately low dose.